2001
DOI: 10.1016/s0735-1097(01)01547-9
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of right heart enlargement after closure of secundum atrial septal defect with transcatheter technique11IRB approval and informed consent were both obtained for placement of the Amplatzer Septal Occluder device.

Abstract: Closure of secundum ASD results in decreased indexed RV volume comparable to that in control subjects at 24 months following closure. Indexed RA area remains increased compared to that in control subjects but does decrease over time. Decrease in RA area is inversely proportional to age at time of ASD closure. Long-term follow-up is required to evaluate the clinical impact of persistently increased RA size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…[16], performed on a group of 38 patients with ages ranging from 1 year to 69 years, are close to those obtained in our study in terms of the parameter values obtained 24 h post-procedure. The cited authors reported a marked decrease of indexed RA surface area during this time; however, the indexed RA surface area did not normalize during the subsequent 2 years of follow-up, while in our study it normalized after 3 months of follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[16], performed on a group of 38 patients with ages ranging from 1 year to 69 years, are close to those obtained in our study in terms of the parameter values obtained 24 h post-procedure. The cited authors reported a marked decrease of indexed RA surface area during this time; however, the indexed RA surface area did not normalize during the subsequent 2 years of follow-up, while in our study it normalized after 3 months of follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…[16] reported normalization of indexed RV volume (RV volume/BSA) in children 2 years after ASD II closure with the ASO. It seems that due to the complexity of the RV geometry, in our opinion, the M-mode dimension alone does not capture the real ongoing changes in RV size after percutaneous closure of ASD and adding two-dimensional measurements could better reflect the ongoing changes.…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have focused on this issue from different aspects. These aspects included the hemodynamic status 15 as well as electrocardiographic, 16,17 functional, [18][19][20][21][22] and volumetric reverse remodeling [23][24][25][26] ; none of which have correlated remodeling to MVP status.…”
Section: Discussionmentioning
confidence: 99%
“…Often there is a rapid decrease of atrial dimensions after ASD closure [6, 7], probably by leading to decrease in wall tension and reduction of the arrhythmic substrate. This is also exemplified by one of the patients in our series, who had been excluded because of persistent AF before ASD closure.…”
Section: Discussionmentioning
confidence: 99%